Upaya Guru dalam Mengatasi Masalah Permasalahan Pembelajaran IPS Pada Era Digital - Enjel Elfrida Purba; Nur Haliza; Jelita Maria Christine; Sayidah Latifah Hanum; Andi Taufiq Umar (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
In research focused on all social studies learning problems at the high school level, where these problems were found based on the journal